2007
DOI: 10.1017/s1474748008000030
|View full text |Cite
|
Sign up to set email alerts
|

Robust Heterodimensional Cycles and $C^1$-Generic Dynamics

Abstract: A diffeomorphism f has a heterodimensional cycle if there are (transitive) hyperbolic sets Λ and Σ having different indices (dimension of the unstable bundle) such that the unstable manifold of Λ meets the stable one of Σ and vice versa. This cycle has co-index 1 if index(Λ) = index(Σ) ± 1. This cycle is robust if, for every g close to f , the continuations of Λ and Σ for g have a heterodimensional cycle.We prove that any co-index 1 heterodimensional cycle associated with a pair of hyperbolic saddles generates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 35 publications
1
130
0
Order By: Relevance
“…Finally, [6, Theorem 4.1] implies that by arbitrarily small C 1 -perturbations these strong homoclinic intersections yield blender-horseshoes for some iterate of the map (stable or unstable, according to the chosen perturbation). We observe that though the terminology blender-horseshoe was not used in [6] the construction corresponds exactly to the prototypical blender-horseshoes in [7,Section 5.1]. In this way, it follows we have shown that having (stable and unstable) blender-horseshoes (for some iterate) is a C 1 -dense property in RTPH 1 (M ).…”
Section: 5mentioning
confidence: 71%
See 1 more Smart Citation
“…Finally, [6, Theorem 4.1] implies that by arbitrarily small C 1 -perturbations these strong homoclinic intersections yield blender-horseshoes for some iterate of the map (stable or unstable, according to the chosen perturbation). We observe that though the terminology blender-horseshoe was not used in [6] the construction corresponds exactly to the prototypical blender-horseshoes in [7,Section 5.1]. In this way, it follows we have shown that having (stable and unstable) blender-horseshoes (for some iterate) is a C 1 -dense property in RTPH 1 (M ).…”
Section: 5mentioning
confidence: 71%
“…In our context, due to the nonhyperbolicity assumption, we have that C 1 -open and -densely in RTPH 1 (M ) the diffeomorphisms have simultaneously saddles of indices dim E ss and dim E ss + 1, this follows from the ergodic closing lemma in [32]. With the terminology in [6,7], the saddles of diffeomorphism in RTPH 1 (M ) have real central eigenvalues (this follows from the fact that dim E c = 1). The robust transitivity assumption and the connecting lemma [25,4] imply that C 1 -densely in RTPH 1 (M ) there are diffeomorphisms with heterodimensional cycles associated to these saddles with real central eigenvalues.…”
Section: 5mentioning
confidence: 91%
“…Bearing in mind the classic constructions of robust homoclinic tangencies and heterodimensional cycles ( [19,7]) via the unfolding of tangencies and cycles associated with saddles, we ask the following: Question 2. Can a diffeomorphism f having a non-transverse heterodimensional cycle associated with saddles P and Q be C r -approximated by a diffeomorphism g with a C r -robust non-transverse heterodimensional cycle associated with hyperbolic sets containing the continuations P g and Q g of P and Q?…”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…Since, by [3], for any X ∈ R 3 , C X (γ) is robustly isolated. So, there exist a neighborhood U(X) of X and a neighborhood U of C X (γ) such that for any Y ∈ U(X),…”
Section: Proof Of Main Theoremmentioning
confidence: 99%